Developing The Menstrual Migraine Symptoms Scale - Ayhan Parmaksız; Meryem Erdoğan; Yasemin Özyer Güvener (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: The objective of this study was to develop the Menstrual Migraine Symptoms Scale (MMSS).Methods: The study utilized a robust methodological design with a sample size of 582 participants. The data underwent a comprehensive analysis employing various statistical techniques, including item analysis, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), Cronbach's alpha internal consistency coefficient, and the Intraclass Correlation Coefficient (ICC) for test-retest reliability.Results: The two sub-dimensions of the scale, consisting of 19 items, demonstrated excellent internal consistency, with Cronbach's alpha coefficients ranging from 0.932 to 0.970. Furthermore, the total scale exhibited a high level of internal consistency, with a Cronbach's alpha coefficient of 0.976. The item correlation values within the scale ranged from 0.741 to 0.921, indicating strong relationships between the items.Conclusion: The study findings conclusively demonstrated the validity and reliability of the MMSS as a robust measurement tool specifically designed for assessing female individuals.